The Impact of Tax and Expenditures Policies on Income Distribution: Evidence from Pakistan - Suhrab Khan; ihtisham Ul haq Padda (ETIKONOMI, 2021)
Tax and social expenditure policies have a crucial role in income distribution. This study explores the potential role of taxation and social expenditure policies in income redistribution in South Asia. For this purpose, empirical analysis is conducted by Fixed Effect (FE) and Instrumental Variable (IV) FE models. The analysis suggests that both taxation and social expenditures policies effectively reduce income inequality in South Asia. These findings indicate that social spending and taxation can be used as a policy tool to redistribute income in developing countries. The results also indicate that higher social spending, increased direct taxes, and more reliance on foreign debts can ameliorate the income distribution. Based on the results, it can be suggested that for this region, with the low level of taxes, direct taxes, a large informal economy, and other weak features of tax administration, more reliance on direct taxes and social expenditure policies should be the primary tool for income redistribution.JEL Classification: H2, H5, I3How to Cite:Khan, S., & Padda, I. U. H. (2021). The Impact of Tax and Social Expenditure Policies on Income Distribution: Evidence from South Asia. Etikonomi, 20(2), xx – xx. https://doi.org/10.15408/etk.v20i2.18121.